Immunogenicity and Safety of a Chemically Synthesized Divalent Group A Streptococcal Vaccine - Yongxiang Wu; Suhua Li; Yanting Luo; Yunyue Zhao; Jiarui Wang; Ruimin Dong; Xujing Xie; Jieming Zhu; Jinlai Liu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Group A streptococcus (GAS) infections and poststreptococcal sequelae remain a health problem worldwide, which necessitates searching for an effective vaccine, while no licensed GAS vaccine is available. We have developed a divalent peptide vaccine composed of 84 amino acids to cover the main GAS serotypes (M1 and M12 streptococci) in China, and herein, we aimed to evaluate immunogenicity and safety of this vaccine. Methods. Mice were immunized with the vaccine. ELISA, indirect bactericidal test, and immunofluorescent assay were used to study immunogenicity. GAS challenge assay was used to test the protective effect. Safety was tested by histopathological analysis. Results. Immunized group mice (n=16) developed higher titer antibody after immunization than nonimmunized group mice (n=16) did. This antibody can deposit on the surface of GAS and promote killing of GAS, resulting in 93.1% decrease of M1 GAS and 89.5% of M12 GAS. When challenged with M1 and M12 streptococci, immunized group mice had a higher survival rate (87.5% and 75%) than nonimmunized group mice (37.5% and 25%). No autoimmune reactions were detected on organs of mice. Conclusion. The results suggest that this vaccine shows fair immunogenicity and safety, which will lead our research on GAS vaccine into clinical trial.